DISCOURSE ANALYSIS DISCOURSE ANALYSIS OF PRESIDENT BARRACK OBAMA’S SPEECH IN AL AZHAR UNIVERSITY - Hadi, M. Wahyu; Masyudi, Masyudi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
The purpose of this research is to analyz what kinds of attitudes showed in President Barrack Obama's speech, how does President Barrack Obama express his attitudes, and how does President Barrack Obama amplify his attitude toward Islam in his Al-Azhar University speech. Based on the data analysis, this research concluded that president Barrack Obama showed the three kinds of attitude namely affect, judgment,and appreciation. The affect dominates the proportion of the attitudes employed in president Barrack Obama's speech 25 sentences it equal to 53%, followed by judgment in the second place'13 sentences it equal to 28%. Appreciation was the least resource of attitude used in the president Obama's speech 9 sentences it equal to 19%. The positive attitude consists of 36 sentences it equals to 77% than negative one consists of 11 sentences it equals to 23%, because he knew that America and Islam have been in tension. In amplifying his attitude the use of focus is more frequents than the force in which 33 sentences in focus and 14 sentences in force. As well as the amplification of President Barrack Obama's attitude tend to focus because America and Islam has been in tension therefore he focused on improving the relationship between America and Islam. As American president who spoke in front of Muslim majority, he was a marvelous leader who could analyze problems and find the solutions.